Early Hospital Readmissions and Mortality in Patients With Decompensated Cirrhosis Enrolled in a Large National Health Insurance Administrative Database. Issue 9 (October 2017) - Scaglione, Steven J.; Metcalfe, Leanne; Kliethermes, Stephanie; Vasilyev, Ivan; Tsang, Rebecca; Caines, Allyce; Mumtaz, Shaham; Goyal, Vik; Khalid, Asra; Shoham, David; Markossian, Talar; Luke, Amy; et al.
Abstract : Background: Patients with decompensated cirrhosis have high rates of morbidity and mortality and frequently require hospital admission. Few studies have examined early readmission as an indicator of 90 day and overall mortality. Analysis of large databases is needed to evaluate the association between early readmission and mortality in decompensated cirrhosis. Methods: We analyzed 5 years of private, employer-based, health insurance claims data associated with HealthCare Services Corporation on 13.5 million members over 4 states from 2010 to 2014. We defined early readmission as an admission to a general acute care hospital within 30 days of an index hospitalization and compared mortality to those who were readmitted after 30 days (late readmission). Univariable analysis was used to compare clinical and patient characteristics associated with early readmission. Cox proportional hazard models with time-varying covariates were used to assess if an early readmission was an independent risk factor for death. Results: A total of 16, 107 patients with decompensated cirrhosis were analyzed. During the study period, 82% of patients with decompensated cirrhosis were hospitalized at least once. Over 50% of hospitalized patients experienced an early readmission. Patients with an early readmission received blood transfusions, transjugular intrahepatic portosystemic shunt, paracentesis, thoracentesis, and upper endoscopies more frequently than those with a late readmission. Cirrhotics with an early readmission had higher rates of hepatorenal syndrome, sepsis, hepatocellular carcinoma, hepatic encephalopathy, and ascites. Patients experiencing an early readmission had greater 90 day, 1 year and overall mortality. Early readmission was an independent predictor of worse survival when adjusting for other conditions associated with mortality in patients with cirrhosis, but the impact of an early readmission dissipated after 1 year. Conclusions: Patients with decompensated cirrhosis have high rates of hospitalization and frequently experience an early readmission. An early readmission to an acute care hospital is an independent predictor of mortality in patients with decompensated cirrhosis for at least 1 year following initial hospitalization.